AB0265 Non-Canonical NF-κB Signaling in Microvessels of Atherosclerotic Lesions in Coronary Arteries Is Associated with Inflammatory Cell Infiltration and Myocardial Infarction. (15th July 2016) - Maracle, C.X.; Agca, R.; Helder, B.; Niessen, H.W.; Nurmohamed, M.T.; Tas, S.W.
Abstract : Background: Patients with chronic inflammatory diseases (CID) have higher risk of developing cardiovascular disease which may be in part due to increased systemic inflammatory burden. In atherosclerosis, extensive neovascularization is associated with plaque instability and increased chance of myocardial infarction (MI). We have established that non-canonical NF-κB signaling, and its central regulator NF-κB inducing kinase (NIK) in endothelial cells (EC) contributes to angiogenesis in synovial tissue of patients with various types of arthritis. Thus, we hypothesized that NIK + EC may also contribute to neovascularization in atherosclerotic lesions. Objectives: Evaluate the expression of NIK in microvessels in atherosclerotic lesions from patients with and without CID and determine if it is associated with inflammatory cell influx, systemic inflammation or involvement of coronary arteries in MI. Methods: Atherosclerotic lesions from 11 individuals with CID along with 11 matched controls, isolated from parts of the coronary artery implicated in MI (CA+) or not (CA-), were immunohistochemically stained with antibodies against NIK, CD31/34 (EC), myeloperoxidase (neutrophils), CD45 (lymphocytes), CD68 (macrophages) and tryptase (mast cells). NIK vessel density (NIK + VD) and immune cell density (ICD) were subsequently calculated. Results: NIK + EC were present in atherosclerotic lesions of all coronary arteries. NIK + VD significantly correlated with ICD of all characterized immune cells: leukocytes (r=0.5227; p<0.0001), macrophages (r=0.3397, p<0.0001), mast cells (r=0.4205, p<0.0001) and neutrophils (r=0.2129, p=0.0016). No significant differences were found in NIK + VD in CID patients versus healthy, however, influx of leukocytes and macrophages per NIK + microvessel was significantly higher in CID lesions. Increased NIK + microvessels were also noted in CA+ as compared to CA- tissues (p=0.0139) in both healthy and CID patients. Conclusions: NIK + microvessels are present in high numbers in atherosclerotic lesions and are strongly associated with the influx of inflammatory cells. Systemic inflammation is not a prerequisite for activation of this pathway in EC in atherosclerotic lesions, but our findings suggest that non-canonical NF-κB signaling is more pronounced in patients with CID resulting in the attraction of more immune cells that may further enhance progression of atherosclerotic lesions. Since activation of the non-canonical NF-κB pathway in EC induces angiogenesis and NIK + vessels are increased in coronary arteries associated with MI, non-canonical NF-κB signaling in EC may drive neovascularization and plaque instability, thus increasing the chance of developing a (fatal) MI. Disclosure of Interest: None declared